PENGARUH SPIRITUAL TEACHING TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN PAI DI SMP PGRI KALIMULYA DEPOK - Saidatul Lathifah Shobur; Siti Rohmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2022)
Immoral phenomena among students are increasingly worrying, such as free sex, narcotics, brawls and other crimes, which is an educational problem that needs attention from all parties, especially schools. This study aims to determine whether or not there is an influence of spiritual teaching on student learning outcomes in grade VIII in PAI subjects at SMP PGRI Kalimulya, Depok. This research is a research with a quantitative approach. Data collection uses a questionnaire and documentation method. The analysis technique used is simple linear regression analysis, by testing the hypothesis using the f test. The results of the data obtained in the f test regarding the effect of spiritual teaching on student learning outcomes in PAI subjects were 13.160. It is proven that by calculating the statistical results with a significance level of 5% with a df of 4.02, H0 is rejected and Ha is accepted, meaning that there is a significant influence between spiritual teaching on student learning outcomes in class VIII in PAI subjects at SMP PGRI Kalimulya. From the results of the determinant (Rsquare) it is concluded that the effect of the variable (X) Spiritual teaching on the variable (Y) of learning outcomes is 19.6% and the remaining 80.4% is influenced by other factorsnot examined by the author